Quantitative physiology and elemental composition of Kluyveromyces lactis CBS 2359 during growth on glucose at different specific growth rates - Dias, Oscar (2018)
The yeast Kluyveromyces lactis has received attention both from academia and industry due to some important features, such as its capacity to grow in lactose-based media, its safe status, its suitability for large-scale cultivation and for heterologous protein synthesis. It has also been considered as a model organism for genomics and metabolic regulation. Despite this, very few studies were carried out hitherto under strictly controlled conditions, such as those found in a chemostat. Here we report a set of quantitative physiological data generated during chemostat cultivations with the K. lactis CBS 2359 strain, obtained under glucose-limiting and fully aerobic conditions. This dataset serve as a basis for the comparison of K. lactis with the model yeast Saccharomyces cerevisiae in terms of their elemental compositions, as well as for future metabolic flux analysis and metabolic modelling studies with K. lactis.